2020
DOI: 10.1590/1806-9282.66.5.590
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin is associated with a prognosis of gastric adenocarcinoma

Abstract: SUMMARY OBJECTIVE Thrombopoietin (THPO) is well-known as a megakaryocyte growth and development factor (MGDF) involved in megakaryocyte proliferation and maturation. To explore the biological effects of THPO in gastric adenocarcinoma, we conducted this study. Methods: By accessing the TCGA database, the expression level of THPO was determined in tumor tissues. The association between THPO expression and clinical features, or prognostic significance was described by Cox regression analysis and Kaplan-Meier. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…J, The levels of ELF3-AS1, hnRNPK, and CCL20 in gastric cancer tissues were positively correlated were potential downstream target genes for ELF3-AS1. Although several studies have reported that tumor tissues and cells can produce THPO,51,52 and we failed to verify the positive correlation between THPO and platelet count in the peripheral blood of GC patients, our research indicates the possibility that the high expression ELF3-AS1 in GC tissues promotes the expression and release of IL-6…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…J, The levels of ELF3-AS1, hnRNPK, and CCL20 in gastric cancer tissues were positively correlated were potential downstream target genes for ELF3-AS1. Although several studies have reported that tumor tissues and cells can produce THPO,51,52 and we failed to verify the positive correlation between THPO and platelet count in the peripheral blood of GC patients, our research indicates the possibility that the high expression ELF3-AS1 in GC tissues promotes the expression and release of IL-6…”
contrasting
confidence: 73%
“… 33 In our study, we found that high ELF3‐AS1 expression was associated with thrombocytosis, and IL6 and THPO were potential downstream target genes for ELF3‐AS1. Although several studies have reported that tumor tissues and cells can produce THPO, 51 , 52 and we failed to verify the positive correlation between THPO and platelet count in the peripheral blood of GC patients, our research indicates the possibility that the high expression ELF3‐AS1 in GC tissues promotes the expression and release of IL‐6 into the blood and stimulates the liver to produce more THPO, or that GC tissues directly produce more THPO, resulting in an increase in blood platelet count. Verification of this hypothesis requires more research.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombopoietin (THPO) is involved in megakaryocyte proliferation and maturation of megakaryocyte growth and development factors. It is overexpressed in GC and causes poor prognosis by affecting cell viability, invasion, and migration [19]. In recurrent GC, elevated UPK1B expression has a worse prognosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Research on CRC and thrombopoietin is limited. Earlier studies have identified that cancer cells can induce circulating thrombopoietin production [ 50 ]; furthermore, higher thrombopoietin level is associated with gastrointestinal cancers, and a possible relationship between more advanced clinical stages and thrombopoietin has been also suggested [ 51 , 52 ]. Similar to the observations above, we found that the thrombopoietin level of CRC patients is higher than those of healthy subjects; however, the effect of thrombopoietin levels over survival was negligible, and no change with the course of the disease could have been identified in either of our longitudinal models.…”
Section: Discussionmentioning
confidence: 99%